New Elements in the Tax Control in Hungary - Pardavi, László (Public Governance, Administration and Finances Law Review, 2017)
The system-wide regulation of taxes in Hungary clearly represents the lawmakers’ constant strive for making the law up-to-date. Currently, Hungary has approximately 60 types of taxes or fees, and it is a huge challenge to fulfill tax policy aims in order to make the regulation suitable for all of them. In recent years, tax authorities – given by the possibilities of the regulation – have introduced numerous, specific tax control methods, while some of these provide interesting legal solutions, but more importantly several of them have significant impact on taxpayers. The study introduces applicational experiences with some of these.